Analysis Of Parking Space Capacity At Karya Nugraha Market - Muhammad Chaiddir Hajia (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
Parking capacity plays an essential role in ensuring the effectiveness of urban transportation systems, particularly in areas characterized by dense economic activity such as Karya Nugraha Market in Baubau City. This study aims to analyze the adequacy and performance of parking facilities by examining static parking capacity, parking accumulation, and utilization levels through the Parking Index (PI) method. Field observations and direct measurements were conducted to obtain data on vehicle volumes, usage duration, and turnover rates in the designated parking areas. The results reveal that the available parking capacity consists of 10 SRP for cars and 168 SRP for motorcycles. During peak activity periods, the maximum parking accumulation reaches the same value as the static capacity for both types of vehicles, resulting in a Parking Index of 100%. This indicates that the parking facilities operate at full saturation and are unable to accommodate additional vehicles entering the market area.The fully saturated parking condition has significant implications for transportation performance, including increased congestion, reduced accessibility, and delays in vehicle movement surrounding the market environment. These conditions negatively impact visitor comfort and disrupt commercial activities. The findings underline the urgent need for improved parking management strategies, such as restructuring vehicle circulation patterns, expanding parking capacity where land availability permits, implementing time-limited parking regulations, and enhancing operational efficiency through clear parking markings and trained personnel. Integrating parking management with broader urban mobility policies is also crucial to ensure long-term sustainability and improved accessibility in the Karya Nugraha Market area.